ANALYSIS OF LOCUTION, ILLOCUTION, AND PERLOCUTION SPEECH ACTS IN SOME HADITHS - Wahyu Unggul Widodo (Journalistics: Journal of English Teaching and Applied Linguistics, 2025)
This study investigates the application of the locutionary, illocutionary, and perlocutionary speech acts within selected Hadiths of Prophet Muhammad (peace be upon Him). The research explains how the Prophet’s sayings give not only informational content but also, they carry intended meanings and specific effects to Muslim. The study is qualitative using content analysis to selected Hadiths retrieved from https://sunnah.com. Four Hadiths were examined to identify the literal utterance (locution), the Prophet’s intended meaning (illocution), and the impact on the listener or Muslim (perlocution). These analyses reveal that Hadiths sometimes use figurative language that need a deeper interpretation and understanding to get their full communicative function. This study explores how speech act theory provides a powerful point of view through which Islamic texts can be understood beyond their literal meanings. By decoding the intentions and effects embedded in prophetic sayings, readers are encouraged to engage more reflectively with religious teachings. The study confirms that Hadiths are rich linguistic sayings capable of guiding both spiritual understanding and ethical behavior through layered speech acts.